Developing Indigenous Australian cultural competence: a model for implementing Indigenous content into curricula - Flavell, Helen; Thackrah, Rosalie; Hoffman, Julie (Curtin University, 2013)
This case study describes the implementation of a stand-alone unit on Indigenous Australian culture and health within a nursing and midwifery program, and presents quantitative and qualitative data from the university's anonymous online student teaching and learning questionnaire. In doing so, this study aims to determine whether a single, compulsory unit has the capacity to develop graduate Indigenous Australian cultural competence. Qualitative data from the nine teaching periods over the five years the unit was taught is analysed to determine student satisfaction and motivation. A total of 1742 students enrolled in the unit over five years and 748 completed the online questionnaire (a response rate of 43%). Qualitative data from the same teaching and learning questionnaire is drawn on to highlight the impact of the unit on student attitudes towards Aboriginal and Torres Strait Islander peoples, as well as the pedagogical approaches adopted to teach compulsory Aboriginal studies to predominately non-Aboriginal students.Data suggests that overall students were satisfied and engaged with the unit. For many the experience was transformative, not having had prior experience with Indigenous Australians or Aboriginal studies' content. A discrete unit on Indigenous culture and health has the capacity to assist students to begin their journey to cultural competence. However, to be successful and sustainable, such a unit must be aligned with the three key areas identified in a Reconciliation Action Plan: relationships, respect and opportunities. Furthermore, key pedagogical approaches are required to ensure students are motivated to engage with the content.